Subcutaneous panniculitis-like T cell lymphoma: a rare entity and its cryptic journey through pregnancy - Singh, Surender; Chikhalkar, Siddhi B.; Shende, Aditi A.; Kharkar, Vidya D.; Oswal, Prateek (International Journal of Research in Dermatology, 2021)
Subcutaneous panniculitis-like T-cell lymphoma (SPTCL) is a rare form of skin lymphoma that primarily is localized to the subcutaneous adipose tissue and accounts for less than 1% of all peripheral T-cell lymphomas. It presents with multiple subcutaneous nodules or plaques on extremities and has poor prognosis if accompanied by hemophagocytic syndrome. Differential diagnosis is panniculitis, lupus panniculitis and leprosy. We report such a rare case of a female with lupus erythematosus (LE) panniculitis like presentation with favourable outcome to oral steroids in pregnancy.